Traces of the Siantar Kingdom in Pematang Village, Simalungun Village, Pematang Siantar City - Ricu Sidiq; Lastiarma Silaban; Mawini Simamora; Yona Febyola Siagian; Ruth Maria Siregar (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
This study aims to find out how the history of the Siantar kingdom traces in the village of Pematang Siantar.Pematang Siantar City is an area that was formerly part of the Siantar kingdom. The Kingdom of Siantar is one of theoldest kingdoms in Simalungun which is a confederation of kings of Maroppat. One of the most famous kings of this kingdom was King Sang Naualuh whose reign brought prosperity to the Simalungun community. This study focuses on the history of the Siantar kingdom and historical relics in the form of sites and buildings that still stand firmly in Pematang Village, Simalungun Village, and Pematang Siantar City. As for conducting this research, the research method used is a historical research method consisting of heuristics, source criticism, interpretation and historiography.